Incumbents' Performance and Political Polarization - Marina Dodlova; Galina Zudenkova (Center for Economic Studies and ifo Institute (CESifo), 2016)
This paper studies the relationship between incumbents' performance and political polarization, both with theory and data. The theory is based on a spatial model of political competition in which the voters use the incumbent's performance in office to update their beliefs about his competence. A better performance leads to the incumbent's electoral advantage and so allows him to announce a more extreme platform closer to his bliss point. Therefore, conditioned on reelection, a better incumbent's performance leads to higher political polarization. We use the data on the incumbents' performance in natural disaster relief and the ideological positions they take in the U.S. House of representatives in 1953-2010. The empirical evidence shows that a better performance in post-disaster recovery is associated with more extreme ideological positions of the corresponding incumbents. These and other empirical results are in line with the model predictions.
Keywords: D72; H84; Q54; 330; political polarization; incumbents' performance; spatial competition; natural disasters